Building digital entrepreneurs in Indonesia: The role of education, competence, and self-efficacy - Ferry Arfiansyah; Suryana Suryana; Hari Mulyadi; Vanessa Gaffar; Rengga Madya Pranata (Jurnal Fokus Manajemen Bisnis, 2025)
As digital transformation progresses, understanding the elements that motivate students in higher education to pursue digital entrepreneurship has become increasingly essential. Indonesia, as one of the largest developing digital economies, provides a vital context where high digital literacy among youth has not yet translated into strong entrepreneurial activity, making its university students a critical population for examining the education–intention gap. Most prior studies addressed digital entrepreneurial education and competence independently, with limited efforts to link them in explaining entrepreneurial motivation. This research analyzes the intermediary influence of digital entrepreneurial self-efficacy in bridging the effects of digital entrepreneurial education and digital competence on students’ entrepreneurial intentions among 173 university students in West Java, Indonesia, utilizing a structural equation modeling approach. Analysis outcomes demonstrate that digital education and competence strengthen students’ confidence to initiate digital ventures. This heightened self-efficacy, in turn, becomes the most decisive factor influencing entrepreneurial intention. Digital competence alone does not directly foster intention but becomes influential when accompanied by strong self-belief, indicating that technical proficiency must be complemented by psychological readiness. The research merges the theory of planned behavior and social cognitive theory to construct its conceptual framework to connect intention development with efficacy processes, illustrating how digital learning and skills collectively foster entrepreneurial motivation. Practically, it highlights the importance of educational designs that simultaneously build competence and confidence to cultivate capable and resilient digital entrepreneurs.